B2B (bull-to-bull) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
B2B (bull-to-bull)A bull in Baringo district, Kenya, has taught other cattle to eat cactus (Opuntia megacantha) as fodder, after the thorns have been burnt off. According to a report from the International Development Research Centre, two years of...